"Why do I have to learn about this?" Understanding Human Rights Education in Icelandic Compulsory Schools - Ársól Clara Arnardóttir 2000- (2024)
Ritgerðin er skrifuð við sagnfræðideild háskólans í Lundi. This thesis explores the state of human rights education (HRE) in Icelandic compulsory schools, through the experiences of teachers. This thesis puts three primary research questions forward (1) what do teachers know about human rights? (2) how do teachers view and use HRE and (3) are they prepared to teach children's rights? To answer these questions, a survey was sent to all Icelandic compulsory schools and four interviews were taken. the findings reveal that Icelandic compulsory school teachers have a good level of knowledge and understanding of children's rights. teachers view HRE as an important aspect of compulsory education and they are prepared to teach it in any subject. Teachers use HRE to develop students' knowledge, skills, understanding of human rights and their attitudes and behaviours of human rights. Iceland has not fully implemented the CRC and being without important elements, such as an independent monitoring body, is not optional any more. this thesis concludes with three crucial recommendations for the betterment of children's rights in Iceland.